Merjenje celičnega imunskega odziva pri okužbi z Borrelio burgdorferi - Malovrh, Tadej (Medicinski razgledi, 1998)
The purpose of this study was to determine the diagnostic value of the lymphocyte blast transformation test in Lyme disease. Our laboratory results were compared with the diagnoses established by physicians. The course of the illness was followed in 213 individuals whose blood samples were tested for cell immunity against Borrelia burgdorferi. All patients showed clinical picture compatible with Borrelia burgdorferi infection. Sixty-five of the 213 patients (30.5%) developed cellular immunity, 4 (1.9o%) showed a non-specific cellular immune response, and 144 patients (67.6%) showed no cellular immune response to Borrelia burgdorferi antigens. The individuals were further divided into 5 groups by their clinical signs. In group 1, cellular immune response was observed in 45.8 per cent of patients, in group 2 in 57.1 per cent, in group 3 in 11.1 per cent, in group 4 22.1 per cent and in group 5 37.2 per cent of patients.
Keywords: Lyme borelioza; Lyme disease; Immunology; imunologija; limfociti; Borrelia burgdorferi; Lymphocyte transformation; Immunity, cellular; Igg; Igm; diagnostika